Effect of metallic nanoparticles on microalgal growth and lipid accumulation for biodiesel production - Oztay, Dilek; Inan, Benan; Kocer, Anil Tevfik; Ozcimen, Didem (SPRINGER HEIDELBERG, 2023)
The study aims to investigate the effects of silver and titanium-oxide nanoparticles on Chlorella minutissima growth and to determine biodiesel production potential of the cultivated microalgae. In this context, C. minutissima were exposed to different concentrations of (5, 10, 25 and 50 mg/L) metallic nanoparticles. The specific growth rate and death rate of microalgae cultures exposed to different concentrations of nanoparticles were calculated and biochemical characterization of microalgae and reactive oxygen analysis were conducted. The experimental results have demonstrated that, inhibition of the microalgal growth increased with increasing concentrations of both nanoparticles. It was found that toxicity on C. minutissima by metallic nanoparticles increased concentration-dependently, and TiO2 nanoparticles were found more toxic than Ag nanoparticles for Chlorella minutissima. On the other hand, up to a certain concentration, lipid composition of microalgal cells were affected in positive way in comparison with the control group. Therefore, it can be suggested that, these nanoparticles may be utilized for increasing the lipid content of microalgae.
Keywords: Silver nanoparticle; Titanium-dioxide nanoparticle; Chlorella minutissima; Toxicity; Biodiesel; TIO2 NANOPARTICLES; FRESH-WATER; SILVER NANOPARTICLES; OXIDATIVE STRESS; CHLORELLA-VULGARIS; ALGAE; ECOTOXICITY; COPPER; INHIBITION; Engineering